2017
DOI: 10.1038/s41598-017-08918-7
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala-centred functional connectivity affects daily cortisol concentrations: a putative link with anxiety

Abstract: The amygdala plays a critical role in emotion. Its functional coupling with the hippocampus and ventromedial prefrontal cortex extending to a portion of the anterior cingulate cortex (ACC) is implicated in anxiogenesis and hypothalamic-pituitary-adrenal (HPA) system regulation. However, it remains unclear how amygdala-centred functional connectivity (FC) affects anxiety and cortisol concentrations in everyday life. Here, we investigate the relationship between daily cortisol concentrations (dCOR) and amygdala-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 54 publications
0
39
0
4
Order By: Relevance
“…Functional connectivity can be defined by the functional co-activation of spatially distributed brain regions ( Tadayonnejad and Ajilore, 2014 ). Along with functional changes in the brain, depression and anxiety are associated with disrupted brain networks ( Gong and He, 2015 ; Tovote et al, 2015 ; Qiao et al, 2017 ), which are responsible for the maladaptive processes underlying these diseases ( Hakamata et al, 2017 ; Rosenbaum et al, 2017 ). Both treatments induced changes in the functional brain map compared with their respective control groups (WT or veh), although the treatments engaged different brain regions, as confirmed by the factors associated with brain activity in the PCA analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional connectivity can be defined by the functional co-activation of spatially distributed brain regions ( Tadayonnejad and Ajilore, 2014 ). Along with functional changes in the brain, depression and anxiety are associated with disrupted brain networks ( Gong and He, 2015 ; Tovote et al, 2015 ; Qiao et al, 2017 ), which are responsible for the maladaptive processes underlying these diseases ( Hakamata et al, 2017 ; Rosenbaum et al, 2017 ). Both treatments induced changes in the functional brain map compared with their respective control groups (WT or veh), although the treatments engaged different brain regions, as confirmed by the factors associated with brain activity in the PCA analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, mice with this genotype exhibit abnormal emotional responses ( Pedraza et al, 2014 ), cognitive alterations in hippocampus-dependent tasks ( Castilla Ortega et al, 2011 , 2014 ), anhedonia ( Moreno-Fernández et al, 2017 ), anxiety ( Santín et al, 2009 ), agitation, increased stress reactivity ( Pedraza et al, 2014 ; Moreno-Fernández et al, 2017 ) dysfunctional coping in response to chronic stress ( Castilla-Ortega et al, 2011 ) and fatigability, behaviours that are strongly associated with the psychopathological endophenotype of depression with anxious features ( Moreno-Fernández et al, 2017 ). Furthermore, from a neurobiological perspective, adult maLPA 1 -null mice exhibit impairments in hippocampal neurogenesis ( Matas-Rico et al, 2008 ), increased endocrine responses to emotional stimuli ( Pedraza et al, 2014 ), hypoactivity and dysregulation of the normal function of the hypothalamic–pituitary–adrenal (HPA) axis after chronic stress ( Castilla-Ortega et al, 2011 ), and dysfunctional changes among the highly interconnected ‘limbic’ regions and functional reorganisation of the brain network ( Moreno-Fernández et al, 2017 ), all of which are factors that have also been strongly correlated with depression ( Boucher et al, 2011 ) and anxiety ( Hakamata et al, 2017 ). Moreover, both the behavioural symptoms and the abnormal patterns of brain connectivity in maLPA 1 -null mice are normalised by antidepressant treatment ( Moreno-Fernández et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reason was that the congruency effects in N2 latency were outcomes of subtracting latency of congruent trials from latency of incongruent trials, However, there might be distinct brain mechanisms for the association between fearful expression processing and testosterone (Van Honk and Schutter, 2006) and cortisol (Watling and Bourne, 2013). Furthermore, a recent study reported that higher daily cortisol concentrations inhibited functional connectivity between the prefrontal cortex and the amygdala when processing fearful faces compared to neutral faces (Hakamata et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This is part of the systemic injury reaction involving a wide range of endocrinological, immunological and haematological effects [12,13]. The sympathetic nervous system (SNS) is activated in times of stress causing a cascade of hormonal and physiological reactions [14]. The hypothalamus activates the SNS, and the adrenal glands release a wave of catecholamines, like epinephrine; this causes tachycardia, hypertension, diaphoresis, increase in respiratory rate and an increase in blood glucose.…”
mentioning
confidence: 99%